2021
DOI: 10.3390/foods10102240
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Performance of Chitosan—Aloe vera Coatings by Adding Beeswax on Postharvest Quality of Mango Fruit

Abstract: The effect of the application of chitosan–Aloe vera coatings emulsified with beeswax (0, 0.5, 1, 1.5 and 2%) during storage of Mangifera indica L. (cv Anwar Ratol) was investigated. Particle size of emulsions was reduced significantly with an increase in beeswax concentration. Water vapor permeability of the coatings was reduced by 43.7% with an increase in concentration of beeswax to 2%. The coated mangoes (at all concentrations of beeswax) exhibited reduced weight loss, delayed firmness loss, minimized pH ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…In the previous studies, chitosan maintained the firmness of the mango fruit [47,56,57]. Amin et al [58] reported that mango fruit firmness was found to decrease linearly with storage time. The rate of firmness loss, however, was consistently decreased with the addition of a up to 2% chitosan-Aloe vera coating.…”
Section: Discussionmentioning
confidence: 91%
“…In the previous studies, chitosan maintained the firmness of the mango fruit [47,56,57]. Amin et al [58] reported that mango fruit firmness was found to decrease linearly with storage time. The rate of firmness loss, however, was consistently decreased with the addition of a up to 2% chitosan-Aloe vera coating.…”
Section: Discussionmentioning
confidence: 91%
“…Coatings can be made of protein, lipid, polysaccharide, resin, or any combination of, as well as originate from both plant and animal sources. During processing, handling, and storage, coating creates a barrier for gases and moisture and also serve as natural delivery systems for postharvest chemicals [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Fruit and vegetables can be treated with soy lecithin-based compounds to delay ripening, maintain firmness, reduce physiological problems, and enhance their appearance and marketability [ 88 , 89 ].…”
Section: Factors Affecting Husk Scald Incidencementioning
confidence: 99%
“…In addition, chitosan nanoparticles positively retain firmness in tomato fruits, limiting the loss of ascorbic acid and phenolic compounds by increasing antioxidant system activity during storage [24]. The application of chitosan-aloe vera coatings to Anwar Ratol mango reduced weight loss, delayed firmness loss, minimized pH change, maintained total soluble solid contents, and retained free radical scavenging activity and total phenolic contents during storage [25].…”
Section: Introductionmentioning
confidence: 99%